Sintering of Hydroxyapatite/Yttria Stabilized Zirconia Nanocomposites under Nitrogen Gas for Dental Materials - C. H. Leong; A. Muchtar; C. Y. Tan; M. Razali; Noor Faeizah Amat (Advances in Materials Science and Engineering)
This study aims to determine the effect of adding 3 mol% yttria stabilized zirconia (3YSZ) in hydroxyapatite (HA) and sintering HA/3YSZ nanocomposites under nitrogen gas on HA decomposition. This paper presents the relationship between microstructure and mechanical properties of HA/3YSZ nanocomposites. Gas pressure and conventional sintering were performed on HA/3YSZ nanocomposites containing different amounts of 3YSZ (i.e., 0, 0.5, 1, and 7 wt%) at 1250°C. The phase stability, morphology, relative density, and microhardness of the HA/3YSZ nanocomposites were investigated. The phase stability of the HA/3YSZ nanocomposites was affected by adding different amounts of 3YSZ. Overall, gas pressure sintering leads to the formation of greater grain size compared with the conventional sintering method. The severe HA decomposition and the presence of the porosity in HA/7 wt% 3YSZ have led to deterioration in relative density and microhardness. In this study, HA/0.5 wt% 3YSZ with gas pressure sintering exhibited the optimum microstructure with the highest relative density (97%) and microhardness (3.93 GPa).